Pemurnian uranil nitrat hasil pelarutan yellow cake menggunakan metoda elektrodialisis - Ghaib Widodo; Guntur Sodikin (PTBN - BATAN, 2015)
Abstract Purification of uranyl nitrate results of dissolution yellow cake using electrodialysis method. Have performed purification of uranium from yellow cake dissolution results and note that the result of condensation in the form of uranyl nitrate/UO2(NO3)2 is still contains impurities and high levels of nitric acid. The purpose of this study is to conduct purification UO2(NO3)2 which still contains impurities by electrodialysis method using a two chamber cell that is cathode and anode chamber and betweenthe chambers inserted two membranes (cation exchange membrane/CEM). Cation exchange membrane serves as a separator between the chamber and also functions as occurcence of ionition. In the process of this electrosialysis using electrodes Pt/Pt (anode and cathode) and the source of electricity supplied from DC power supply. The parameters applied in this uranium purification process using three (3) parameters, acidity ie feed, voltage, and time. In the cathode chamber filled nitric acid (1 N) to bind the uranium ion dioxide into uranyl nitrate in the cathode chamber. The magnefull of the voltage parameters between 3 to 7 volts. While the timing parameters used are from 30 to 120 minutes which interval of 30 minute interval). The best conditions of the electrodialysis process the results obtained at a voltage of 6 volts and a time of 60 minutes at 0.9995 N acidity with the recovery uranium levels in the cathode chamber at 0.0745 g U / L (74.5 mg) or the results obtained in the purification process of purifying uranium from the leaching yellow cake in the cathode chamber of 18.0625 % with high levels of impurities contains in the uranium meet the threshold when used as fuel. Keywords : Purification, electrodialysis, electrode, cation exchange membrane, uranium Abstrak Pemurnian uranil nitrat hasil pelarutan yellow cake menggunakan metoda elektrodialisis. Telah dilakukan pemurnian uranium hasil pelarutan yellow cake dan diketahui bahwa hasil pelarutan berupa uranil nitrat/UO2(NO3)2 tersebut masih berimpuritas dan kadar asam nitrat yang tinggi. Tujuan penelitian ini adalah melakukan pemurnian UO2(NO3)2 dengan metoda elektrodialisis menggunakan alat sel dua bilik yaitu bilik katoda dan anoda dan diantara keduanya disisipkan membran (membran tukar kation/MTK). Membran tukar kation berfungsi sebagai pemisah antar bilik dan sekaligus berfungsi sebagai media perpindahan ion (migrasi). Dalam proses elektrodialisis ini menggunakan elektroda Pt/Pt (anoda dan katoda) dan sumber listriknya disuplai dari DC power. Parameter yang diterapkan dalam proses pemurnian uranium ini menggunakan 3 (tiga) parameter yaitu keasaman umpan, tegangan, dan waktu. Di dalam bilik katoda diisi asam nitrat (1 N) untuk mengikat ion uranium dioksida menjadi uranil nitrat di dalam bilik katoda. Parameter tegangan antara 3 hingga 7 Volt, sedangkan parameter waktu yang digunakan dari 30 hingga 120 menit dengan interval 30 menit. Kondisi terbaik dari proses elektrodialisis hasil yang diperoleh pada tegangan 6 Volt dan waktu 60 menit pada keasaman 0,9995 N dengan kadar uranium yang terpungut dalam bilik katoda sebesar 0,0745 g U/L (74,5 mg). Hasil yang diperoleh dalam proses pemurnian uranium dari hasil pelarutan yellow cake di bilik katoda sebesar 18,0625 % dengan kadar impuritas yang terkandung di dalam uranium telah memenuhi syarat untuk digunakan sebagai bahan baku pembuatan bahan bakar . Kata Kunci : Pemurnian, elektrodialisis, elektroda, membran tukar kation, uranium